'Materially social' critical realism: an interview with Dave Elder-Vass. Issue 2 (15th March 2022) - Elder-Vass, Dave; Morgan, Jamie
ABSTRACT: In this wide-ranging interview, Dave Elder-Vass discusses his main contributions to critical realist theory over two decades. In the first half, he explains his early work on emergence, agency, structure, the concept of culture and norm circles, as well as his work on a broad array of social theorists and positions. Sometimes this has involved differences with other realists, including Tony Lawson, Margaret Archer, Alison Sealey and Bob Carter, which he also comments on here. In the second half, he discusses the common themes of his two most recent books (focused on economic form and value respectively) and current project (focused on the concept of profit), in which he is developing a critical realist approach to political economy.